Gardener demographics, experience, and motivations drive differences in plant species richness and composition in urban gardens - Stacy M. Philpott (Resilience Alliance, 2020)
Urban agriculture has received considerable attention for its role in supporting biodiversity and ecosystem services, and health and well-being for growing urban populations. Urban gardens managed with agroecological practices and higher plant diversity support more biodiversity and may support higher crop production. Plant selection in gardens is a function of temperature and environmental conditions and also depends on gardener socio-demographic characteristics, motivations for gardening, and gardening experience. In this study, we examined how plant richness and composition vary with gardener socio-demographic factors, gardening experience and garden use, and gardener motivations. We focused on the socio-demographic factors of age, gender, education, and region of national origin, used information on years spent gardening and hours spent in gardens as a proxy for gardening experience, and collected information on motivations, as well as crop and ornamental plants grown by individual gardeners. We found that gender, region of origin, time spent gardening, and gardener motivations all influenced plant richness or composition. Specifically, women plant more plant species than men, especially of ornamental plants, and individual gardeners motivated by nature connection tend to plant strongly different plant compositions in their gardens. We also found that region of national origin strongly influences crop composition. In contrast to previous studies, we did not find that gardeners more motivated by food grow a higher proportion of or more crop species compared with ornamentals. Thus we show that multiple socio-demographic characteristics and motivations influence garden plant communities, and thus assuring access to gardens for all groups may boost plant richness and support ecosystem services in gardens.